New advances in beta-blocker therapy in heart failure - Barrese, Vincenzo; Taglialatela, Maurizio (Frontiers in Physiology, 2013)
The use of -blockers (BB) in heart failure (HF) has been considered a contradiction for many years. Considering HF simply as a state of inadequate systolic function, BB were contraindicated because of their negative effects on myocardial contractility. Nevertheless, evidence collected in the past years have suggested that additional mechanisms, such as compensatory neuro-humoral hyperactivation or inflammation, could participate in the pathogenesis of this complex disease. Indeed, chronic activation of the sympathetic nervous system, although initially compensating the reduced cardiac output from the failing heart, increases myocardial oxygen demand, ischemia and oxidative stress; moreover, high catecholamine levels induce peripheral vasoconstriction and increase both cardiac pre- and after-load, thus determining additional stress to the cardiac muscle (1). As a consequence of such a different view of the pathogenic mechanisms of HF, the efficacy of BB in the treatment of HF has been investigated in numerous clinical trials. Results from these trials highlighted BB as valid therapeutic tools in HF, providing rational basis for their inclusion in many HF treatment guidelines. However, controversy still exists about their use, in particular with regards to the selection of specific molecules, since BB differ in terms of adrenergic -receptors selectivity, adjunctive effects on -receptors, and effects on reactive oxygen species and inflammatory cytokines production. Further concerns about the heterogeneity in the response to , as well as the use in specific patients, are matter of debate among clinicians. In this review, we will recapitulate the pharmacological properties and the classification of BB, and the alteration of the adrenergic system occurring during HF that provide a rationale for their use; we will also focus on the possible molecular mechanisms, such as genetic polymorphisms, underlying the different efficacy of molecules belonging to this class.